Photorelease of incarcerated guests in aqueous solution with phenacyl esters as the trigger - Jagadesan, Pradeepkumar (2015)
We report the clean, efficient photorelease of a series of carboxylic acids embedded in octa acid (OA) host and protected by a p-hydroxyphenacyl cage. A key role is played by the cage by providing hydrophobicity for entry into the OA enclosure and yet readily removable as a photoactivated protecting group for release from the host. The rapid photo-Favorskii rearrangement of the departing chromophore does not react with the host OA but diminishes hydrophobicity of the OA contents, leading to their facile release into the solvent.